Empowering Women Ex-Migrant Workers and Domestic Violence Victims through Komunitas Perempuan Singkong Jaya - Chawa, Anif Fatma; Budi Nugroho, Arief; Sutopo, Dhanny Septimawan (Departement of Communication and Community Development Sciences, Faculty of Human Ecology, 2020)
This article seeks to understand the empowerment of women ex-migrant workers who have faced various problems before, during and after going back to the homeland as ex-migrant workers. These problems include unemployment, family’s affairs, exploitation, discrimination and domestic violence. Komunitas Perempuan Singkong Jaya has been established to carry out empowerment programs to overcome these problems. The purpose of this study is to identify the needs as well as the problems that hinder the implementation of the programs and seeks to find the solutions. This study employs descriptive qualitative approach to examine the implementation of the development programs which have been conducted by Komunitas Perempuan Singkong Jaya located in Desa Sukowilangun, Kec. Kalipare, Kab. Malang. Based on the findings, there are several problems in the implementation of development programs, including the lack of capital and facilities, packaging and marketing, as well as product license problems. Addressing these problems, some intervention programs have been conducted, including training and funding which have generated intended outputs. However, this study also found that the change in lifestyle of these women ex-migrant workers has resulted in their being reluctant to be involved in the development programs.